1987
DOI: 10.1093/sleep/10.5.486
|View full text |Cite
|
Sign up to set email alerts
|

Do Nocturnal Penile Tumescence Recordings Alter Electroencephalographic Sleep?

Abstract: While concurrent monitoring of sleep is considered to be a necessary component of evaluating nocturnal penile tumescence (NPT), in order to ensure that NPT data are not invalidated by fragmented sleep or diminished REM sleep, it is not known whether NPT recording itself disrupts sleep beyond the expected first night effect. In this study of 42 outpatient men with major depression and 36 normal control subjects, we found no effect of NPT recording on measures of sleep continuity, proportion of NREM to REM sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In an earlier study, the same group had found diminished sexual interest and satisfaction in men during depressive episodes despite normal reported levels of sexual activity [10]. They have also reported reductions in NPT measures in approximately 25-30% of men in an episode of major depression [8,11,12]. The remitted patients were more satisfied with their sex lives after treatment, despite the relative absence of change in level of daily sexual activity.…”
Section: Sexual Functioning In Depressed Patientsmentioning
confidence: 89%
See 1 more Smart Citation
“…In an earlier study, the same group had found diminished sexual interest and satisfaction in men during depressive episodes despite normal reported levels of sexual activity [10]. They have also reported reductions in NPT measures in approximately 25-30% of men in an episode of major depression [8,11,12]. The remitted patients were more satisfied with their sex lives after treatment, despite the relative absence of change in level of daily sexual activity.…”
Section: Sexual Functioning In Depressed Patientsmentioning
confidence: 89%
“…Partners of depressed men reported less frequent sexual intercourse, more variability in baseline (pre-depression) frequency of coitus, but about equally frequent pleasurable acceptance by the patient before the illness set in, similar total duration of sexual activity, and higher frequency of ED while depressed, but not while well. In another study of the same group [8], depressed men showed diminished nocturnal penile tumescence (NPT) scores.…”
Section: Sexual Functioning In Depressed Patientsmentioning
confidence: 95%